Two-Line Cottage Cotton - Adahamovich, Abdurahmonoa Ilhomjon; Abdumannobovich, Janibekov Dilyorbek (European Journal of Life Safety and Stability (2660-9630), 2021)
Recently, in a number of cotton-growing countries, research has been carried out on the cultivation of cotton with an increased plant density. The purpose of using thickened crops in conditions of a high degree of mechanization of cotton growing is to obtain the largest amount of cotton from a unit area with the least labor and cost, to accelerate the ripening of the crop and improve the quality of fiber.